2021
DOI: 10.3389/fonc.2021.588811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Five Glycolysis-Related Gene Signature and Risk Score Model for Colorectal Cancer

Abstract: Metabolic changes, especially in glucose metabolism, are widely established during the occurrence and development of tumors and regarded as biological markers of pan-cancer. The well-known ‘Warburg effect’ demonstrates that cancer cells prefer aerobic glycolysis even if there is sufficient ambient oxygen. Accumulating evidence suggests that aerobic glycolysis plays a pivotal role in colorectal cancer (CRC) development. However, few studies have examined the relationship of glycolytic gene clusters with prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…Our univariate Cox regression analysis results show that T, N, and M stages were all risk factors of rectal cancer prognosis. However, after including other prognostic variables, only the N stage could independently predict patients' prognosis, consistent with previous studies (Di et al, 2020;Zhu et al, 2021). Our data indicate that more reliable prognostic markers be included in the clinic.…”
Section: Discussionsupporting
confidence: 90%
“…Our univariate Cox regression analysis results show that T, N, and M stages were all risk factors of rectal cancer prognosis. However, after including other prognostic variables, only the N stage could independently predict patients' prognosis, consistent with previous studies (Di et al, 2020;Zhu et al, 2021). Our data indicate that more reliable prognostic markers be included in the clinic.…”
Section: Discussionsupporting
confidence: 90%
“…The DEGs were validated using the following cutoffs: |log2FC| ≥ 1 and FDR <0.05. The linear models for microarray data (LIMMA) R package was performed for DEGs identified between paracancerous and cancer samples as we reported before ( Zhu et al, 2021 ). p values were adjusted using the Benjamini & Hochberg (BH) multiple testing correction.…”
Section: Methodsmentioning
confidence: 99%
“…Up till now, the effects of ENO3 on tumors remain controversial, and its effects might be different depending on a variety of cell types. For example, previous researches reported that ENO3 was highly expressed in STK11 mutant lung cancer, colorectal cancer, and its ectopic expression correlated with a worse outcome of patients by bioinformatic analysis ( Park et al, 2019 ; Zhu et al, 2021 ). However, the results were converse in pancreatic carcinoma and HCC ( Liu et al, 2019 ; Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these, ENO3 has also been involved in various tumors, though the results are contradictory. For example, ENO3 is up-regulated in STK11 mutant pulmonary carcinoma ( Park et al, 2019 ) and colorectal carcinoma ( Xiaohang et al, 2020 ; Zhu et al, 2021 ), while down-regulated in pancreatic cancer ( Tan et al, 2020 ) and hepatocellular carcinomas ( Liu et al, 2019 ). Interestingly, down-regulation of ENO3 is also found in the activated human hepatic stellate cells, which can induce liver fibrosis and cirrhosis ( Zhong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%